On the prime radical of a module over a noncommutative ring - TEKİR, ÜNSAL (MATHEMATICAL SOC REP CHINA, 2004)
Let R be a ring and M a left R.-module. The radical of M is the intersection of all prime submodules of M. It is proved that if R is a hereditary, noetherian, prime and non right artinian and M a finitely generated R-module then the radical of M has a certain form.
Keywords: prime submodule; hereditary rings; Noetherian rings